A clinico-epidemiological study of psoriasis patients with moderate to severe plaque type in tertiary care centre in South India - Sekar, Suganya; Daniel, Samuel J. (International Journal of Research in Dermatology, 2020)
Background: Psoriasis is a chronic disorder with the most common manifestation being the plaque-type. Nearly 20% of the plaque type suffer from a disease of moderate to severe intensity with immense effect on the quality of life. Aim was to study the clinical, socio-economic and demographic characteristics of patients with moderate to severe plaque type of psoriasis. Methods: This was an observational study conducted in about fourty patients diagnosed with moderate to severe plaque type of psoriasis based upon the clinical history, morphology of the lesions and assessed using psoriasis area and severity index (PASI), dermatology life quality index (DLQI) scoring and for comorbidities. Data was compiled and analyzed with statistical package for social science (SPSS) Version 20.0. Results: Mean age was 37.43±10.1 years. 22 were males (55%) and 18 were females (45%). The mean duration was 8.93 years and 15% had family history. The mean age of onset was earlier in the females (20.23 years) with a positive family history, as compared to males (25.36 years). About 62.5% had moderate psoriasis and 37.5% had severe psoriasis. At the baseline the PASI score was 31.98±6.08 and DLQI score was 36. About 67.5% had nail changes and 10% had psoriatic arthritis. Almost in half (47.5%) the duration of the disease was 1 to 5 years and scalp (32.5%) the most common initial site of involvement. Various comorbidities were documented, 72% in moderate psoriasis and 73.33% in severe psoriasis with dyslipidemia (67.5%) being commonest. Conclusions: Patients with moderate to severe psoriasis mostly have a low quality of life with multiple significant co-morbidities that increases the risk for morbidity and mortality.